Home work \( \begin{array}{ll}\text { a) } \frac{x-b}{x^{2}-4}-\frac{2}{x-2}=\frac{-1}{x+2} & \text { (b) } \frac{x^{2}-1}{x+1}=-2\end{array} \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
To solve part (a) of the homework, first notice that \(x^2 - 4\) can be factored into \((x - 2)(x + 2)\). We can rewrite the equation as: \[ \frac{x - b}{(x - 2)(x + 2)} - \frac{2}{x - 2} = \frac{-1}{x + 2} \] To combine the fractions, find a common denominator, which is \((x - 2)(x + 2)\). Rewrite the second term to include this denominator: \[ \frac{x - b - 2(x + 2)}{(x - 2)(x + 2)} = \frac{-1(x - 2)}{(x - 2)(x + 2)} \] Now equate the numerators: \[ x - b - 2x - 4 = -x + 2 \] Combine like terms and solve for \(b\): \[ -x - b - 4 = -x + 2 \] \[ -b - 4 = 2 \] \[ -b = 6 \Rightarrow b = -6 \] Now, moving to part (b), we start with: \[ \frac{x^2 - 1}{x + 1} = -2 \] Multiply both sides by \(x + 1\) (assuming \(x \neq -1\)): \[ x^2 - 1 = -2(x + 1) \] This simplifies to: \[ x^2 - 1 = -2x - 2 \Rightarrow x^2 + 2x + 1 = 0 \] Factoring gives us: \[ (x + 1)^2 = 0 \] This leads to the solution: \[ x + 1 = 0 \Rightarrow x = -1 \] However, \(x = -1\) makes the denominator of the original equation equal to zero, meaning we need to check if it's a valid solution. Since it's not valid, we state that there are no solutions for part (b).